Bubbles : examination of facial emotions and cultural differences in emotion recognition - Ong, Si Hui (2014)
This study aims to examine the facial regions important for identification of six emotions (happiness, sadness, disgust, anger, surprise and fear) and to investigate if there exist cultural differences in how Asians and Westerners recognise facial emotions. The study hypothesised that the eyes and mouth regions are the most useful areas for emotion identification and that Asians are more likely than Westerners to place emphasis on the eyes. Ten participants were recruited for this study. Half of them are Singaporeans (Asian sample group) and the other